Bioinformatics analysis and validation of the critical genes associated with adamantinomatous craniopharyngioma - Fang, Chao; Zhou, Lin; Huang, Hui; Xu, Hai Tong; Hong, Tao; Zheng, Su Yue (Frontiers in Oncology, 2022)
Adamantinomatous craniopharyngioma (ACP) is an epithelial tumor that arises when Rathke's pouch remains during embryonic development. The pathogenesis of ACP remains unclear, and treatment options are limited. Here, we reveal the critical genes expressed in ACP and provide a basis for further research and treatment. The raw dataset GSE94349 was downloaded from the GEO database. We selected 24 ACP and 27 matched samples from individuals with no documented tumor complications (control group). Then, we screened for differentially expressed genes (DEGs) to identify key signaling pathways and associated DEGs. A total of 470 DEGs were identified (251 upregulated and 219 downregulated). Hierarchical clustering showed that the DEGs could precisely distinguish the ACP group from the control group (CG). Gene Ontology (GO) enrichment analysis indicated that the upregulated DEGs were mainly involved in cell adhesion, inflammatory responses, and extracellular matrix management. The downregulated DEGs were primarily involved in cell junction and nervous system development. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that the critical pathway was pathways in cancer. In the PPI network, CDH1, SHH, and WNT5A had the highest degrees of interaction and were associated with the formation of ACP. CDH1 was verified as a critical gene by quantitative reverse transcription-polymerase chain reaction (qRT‒PCR) in ACP and CG samples. We found that CDH1 may play an important role in the pathways in cancer signaling pathway that regulates ACP development. The CDH1 gene may be a target for future research and treatment of ACP.